From support to recovery: the evolving role of LVAD in reversing heart failure - Bingqi Sun; Zhigang Liu (Journal of Cardiothoracic Surgery)
Abstract In recent years, the use of Left Ventricular Assist Devices (LVAD) in the treatment of heart failure has been increasingly widespread. Not only do they provide circulatory support for patients, but the reverse biological changes in myocardial tissue induced by LVAD have led to the recovery of heart function in some patients, allowing for the removal of the device—which termed bridge to recovery (BTR). Despite promising prospective studies reporting LVAD explantation rates exceeding 48–60% in BTR-focused cohorts, real-world registries (e.g., INTERMACS) demonstrate explantation rates below 5%, underscoring critical gaps in patient selection, standardized assessment protocols, and integration of optimized pharmacological and mechanical unloading strategies. This review synthesizes contemporary clinical and molecular insights into LVAD-mediated myocardial recovery. Clinically, key determinants of successful BTR include stringent hemodynamic and echocardiographic criteria for explantation (e.g., LVEF > 45%, PCWP ≤ 15 mmHg), and aggressive guideline-directed medical therapy (GDMT), particularly neurohormonal blockade. Mechanistically, LVAD unloading promotes reverse remodeling through metabolic reprogramming (e.g., enhanced pyruvate-lactate axis activity), restoration of calcium homeostasis, extracellular matrix modulation, and immune-mediated pathways. However, challenges persist, including the lack of predictive biomarkers, suboptimal GDMT adherence, and unresolved debates regarding concomitant cardiac procedures. Emerging evidence highlights the potential of novel pharmacotherapies (e.g., SGLT2 inhibitors, vericiguat) and individualized pump-speed algorithms to augment recovery. Pediatric populations exhibit unique recovery dynamics, with myocarditis and smaller body surface area correlating with higher explantation success. Partial cardiac recovery, observed in over 30% of LVAD recipients, warrants tailored therapeutic strategies to transition to full recovery. Future directions demand multicenter registries integrating molecular profiling with clinical outcomes, standardized BTR protocols, and exploration of adjuvant therapies. By redefining BTR as an achievable goal rather than a rare exception, this paradigm shift could transform advanced heart failure management, offering patients liberation from lifelong device dependency.